(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Currently, the demand for environmentally friendly products made from natural resources is increasing sharply. This requires rational use of natural resources, finding new sources of resources and recycling natural resources out of circulation. Taking into account the above, this article is devoted to the results of research on the processing of secondary fibrous waste, that is, waste paper. MC-3 waste paper is a high-quality secondary resource, as it consists of books, magazines and archival papers, but the presence of typography paint in it limits the possibility of using this secondary raw material. The results of the research presented in the article are the conversion of fatty-waxy substances, which are considered as binders of typography paint in MC-3 waste paper, into a soluble state by the alkaline boiling method, and by emulsifying the dissolved binders under the action of surfactants, from the fiber composition. The process of removing oily-waxy substances from secondary fiber waste by making them soluble was checked by the capillarity of the paper samples taken from it, the effect of the alkaline boiling process on the mechanical strength of secondary fiber waste was controlled by the degree of polymerization of the raw material.